ANALISIS KINERJA KEUANGAN PERUSAHAAN DENGAN METODE ECONOMIC VALUE ADDED (EVA) PADA TOKO ANNISA - mirce kakanga; Ahmad Tomu (Unit Pengelola dan Pengembangan Jurnal Ilmiah dan Informasi (UPPJII) STIE Jambatan Bulan, 2021)
This study aims to determine financial performance with the Economic Value Added (EVA) method at Annisa’s Store during 2019. The research method used is descriptive method. This study uses quantitative data obtained from Annisa’s Store which is then analyzed using the Economic Value Added (EVA) method. The indicators of EVA methods in measuring store financial performance include Net Operating Profit After Tax (NOPAT), Invested Capital, Weight Average Cost Of Capital (WACC), and Capital Charges. The results showed that the financial performance of the January - June period was negative, meaning that during this period the company had not been able to create added value, this was because the NOPAT value obtained was smaller than the Capital Charges. However, in the July - December period it has increased so that it has positive value, meaning that the company is able to create added value.